Agrometeorological Observatory - Establishment and General Maintenance - Kumar, K. Ashok; Sudheer, K.V.S.; Naik, L. Pavan; Reddy, B. Sahadeva (Chronicle of Bioresource Management, 2023)
In recent years, the impact of climate on agricultural production has been gaining importance in the context of global climate change. Higher accuracy in weather data is essential for data analysis to draw valid conclusions scientifically and subsequently to develop climate resilient technologies. Numerous agrometeorological weather stations have been established in many parts of the country to record weather data for various uses. Hence, the real time weather parameters in agrometeorological observatories need to be recorded with utmost care without deviation from recording the actual weather condition. This can be achieved only by proper maintenance of the agrometeorological observatory so that the influence of external/surrounding factors is reduced to the maximum extent. This paper discussed various types of agrometeorological observatories, instruments for recording various weather parameters, guide lines for establishment of agrometeorological observatory and its maintenance that simulate the surrounding agro-ecological conditions.